Best practice in early psychosis intervention for Australian indigenous communities: indigenous worker consultation and service model description. (June 2013) - Catts, Stanley; O'Toole, Brian; Neil, Amanda; Harris, Meredith; Frost, Aaron; Eadie, Kathy; Evans, Russell; Crissman, Belinda; McClay, Jennifer; Shorey, Travis
Objective: The aim of this study was to identify promising elements of best practice relevant to mainstream mental health service (MHS) delivery of early psychosis intervention (EPI) to Indigenous communities. In a companion paper, a comprehensive literature review identified a promising service model with potential for delivering EPI: an Indigenous sub-team embedded within a mainstream health service. Method: This paper describes a consultation process with Indigenous Mental Health Workers (IMHWs) in south eastern Queensland. A case study of the Sunshine Coast Cultural Healing Program (CHP-SC) was carried out during the consultation process. Results: IMHWs agreed that the Australian clinical guidelines for early psychosis were relevant to improving outcomes for Indigenous patients. IMHWs unanimously identified the CHP-SC as a best practice mainstream MHS for delivering EPI. The CHP-SC, which represented an Indigenous sub-team model, was found to be associated with substantially improved engagement of Indigenous young people. Conclusions: We provisionally conclude that specialist EPI could be delivered by specialist Indigenous sub-teams (rather than specialist EPI teams) embedded in mainstream MHSs that incorporate culturally safe practice and are fully integrated with Indigenous primary care services, and recommend that the model be formally evaluated.